Problems faced by students in online learning and their implications for guidance and counseling services - Milatus Solihah; Mudjiran Mudjiran; Zadrian Ardi (Universitas Negeri Padang, 2020)
This research is motivated by a phenomenon in the field that still found students who have problems following the online learning process. One of the causes of problems in learning is personal problems in self-motivation. This study aims to see how the students' problems in the online learning process are described in the midst of the Covid-19 pandemic. The research method used is a quantitative descriptive approach. The study population was 499 students of guidance and counseling batch 2018-2019, Padang State University, with a sample of 125 students, who were selected by simple random sampling technique. Data collection used student problem questionnaires in online learning with a Likert scale model. Data processing using Microsoft Excel. The results of this study indicate: (1) student problems before implementing online learning are in the medium category with a score of 63 and a percentage of 50.4%, (2) student problems when carrying out online lectures are in the high category with a score of 70 and a percentage of 56%, (3) student problems after carrying out online lectures are in the high category with a score of 49 and a percentage of 39.3%. Based on the research findings, it is suggested that the course supervisor lecturers be able to apply various learning applications to students so that online lectures are more effective and for counselors to be able to provide guidance and counseling services in the form of information services, content mastery services, individual counseling services, group guidance services and counseling. groups to students in order to assist students in alleviating the problems or obstacles they experience.